2020
DOI: 10.1101/2020.01.22.914994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breastmilk-promoted bifidobacteria produce aromatic amino acids in the infant gut

Abstract: 26Breastfeeding profoundly shapes the infant gut microbiota, which is critical for early life immune 27 development. However, few breastmilk-dependent microbial metabolites mediating host-microbiota 28 interactions are currently known. We here demonstrate that breastmilk-promoted Bifidobacterium 29 species convert aromatic amino acids (tryptophan, phenylalanine and tyrosine) into their respective 30 aromatic lactic acids (indolelactate, phenyllactate and 4-hydroxyphenyllactate) via a previously 31 unrecogni… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 108 publications
(155 reference statements)
1
52
0
Order By: Relevance
“…Apart from the microbe to microbe interactions, recent studies have revealed that B. bifidum has immunomodulatory activity by inducing regulatory T-cells by microbe-host interaction with its cell-surface polysaccharides [98]. The production of indole lactic acid, an AhR ligand, by infant gut-associated Bifidobacterium species, including B. bifidum, was also recently reported [8,99]. Further investigation is needed to understand the physiology of this species in the gut ecosystem and its role in host interactions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Apart from the microbe to microbe interactions, recent studies have revealed that B. bifidum has immunomodulatory activity by inducing regulatory T-cells by microbe-host interaction with its cell-surface polysaccharides [98]. The production of indole lactic acid, an AhR ligand, by infant gut-associated Bifidobacterium species, including B. bifidum, was also recently reported [8,99]. Further investigation is needed to understand the physiology of this species in the gut ecosystem and its role in host interactions.…”
Section: Discussionmentioning
confidence: 97%
“…These "first colonizers" are believed to confer various beneficial effects on human health, including protection against pathogen infection [2,3], nutritional supplementation [4], reduced inflammation [5,6], and the development of the immune system [7]. Notably, a recent research revealed that bifidus-flora formation is associated with the increased fecal concentration of indole lactic acid, a ligand of arylhydrocarbon receptor (AhR) [8]. In the Bifidobacterium genus, four species, i.e., Bifidobacterium bifidum, Bifidobacterium breve, Bifidobacterium longum ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial metabolites would necessarily need to travel in the blood (or lymph) and through the blood-brain barrier to interact with the brain. In our study, some detected metabolites could partly derive from gut microbiota activity such as DL-Indole-3-lactic acid (ID3461, [99,100] Lastly, we found that month of birth explains a significant variation in metabolomic profiles of newborns (Figure 3b, Figure 4). Whether there is a yearly cyclic pattern or whether our findings are specific to 2005 remains to be determined.…”
Section: /42mentioning
confidence: 57%
“…Alternatively, the absolute abundance of B. infantis EVC001, independent of microbiome composition, correlated with decreased proinflammatory cytokine profiles, which indicates a benefit in feeding B. infantis EVC001 and may support the hypothesis that B. infantis-derived bacterial metabolites, produced through the utilization of HMOs, induce mucosal immune tolerance in the gut [49,58]. Notably, Bifidobacterium-derived acetate has previously been shown to mitigate the pathogenesis of Enterobacteriaceae infection in an animal model [57], and B. infantis-derived indole-3-lactic acid production reduced pathogen-induced inflammation in enterocytes in vitro [49,58] through activation of the aryl hydrocarbon receptor [49,59]. Recently, differences in B. infantis HMO utilization loci have been identified [60], and strains missing key genes involved in HMO utilization are unlikely to confer the same benefits to infants as we observed here, as the conversion of indigestible HMOs to infant accessible short chain fatty acids and indole-3-lactic acid are key functions of a healthy gut microbiome, whether in term or preterm infants [23].…”
Section: Discussionmentioning
confidence: 99%